Effects of AM/PM Diets on Laying Performance, Egg Quality, and Nutrient Utilisation in Free-Range Laying Hens - Jahan, A; Dao, TH; Morgan, Natalie; Crowley, T; Moss, A (MDPI AG, 2024)
Laying hen nutrient requirements change throughout the day, due to the cyclic nature of egg formation. Generally, more energy and protein are required in the morning when the albumen is deposited around the yolk, and more calcium is required in the evening when the eggshell is formed. The aim of this study was to determine if feeding laying hens diets tailored to their specific nutritional and physiological requirements throughout the day, by feeding higher levels of protein and energy in the morning and higher levels of calcium in the evening, is more beneficial than feeding one diet all day. Hy-Line Brown laying hens (n = 360) were housed in free-range floor pens (18 pens with 20 hens/pen) from 34 to 53 weeks of age (WOA). Half of the birds (n = 180, nine replicate pens) were fed a conventional layer hen diet all day (control) and the remaining birds (n = 180, nine replicate pens) were fed an AM diet from 08:00 h to 16:00 h and PM diet from 16:00 h to 08:00 h (AM/PM). From 39 WOA, hens were given access to an outdoor range from 09:00 h to 18:00 h via pop holes. Egg weight and hen-day egg production were measured daily, and feed consumption and the feed conversion ratio (FCR) were measured weekly. Hen weight and egg size uniformity were determined at 43 and 53 WOA, and egg quality was measured at 53 WOA. A total of 72 hens (4 hens/pen, 36 hens/treatment) were euthanised at 53 WOA to determine ileal apparent energy and nitrogen digestibility. A cost–benefit analysis for the study period, based on feed costs and egg mass, was calculated. Overall, the results showed that the AM/PM treatment increased egg mass by 2.15% (60.4 vs. 59.1 g/hen/day, p = 0.086) and improved feed efficiency by 8.34% (2.231 vs. 2.436 kg feed/kg egg, p = 0.030) compared with the control. A higher yolk colour score was observed in eggs from hens on the AM/PM treatment (p = 0.002), but no other significant effects of the treatments on egg quality were observed. Ileal digestible energy and digestible nitrogen coefficient were lower in hens on the AM/PM treatment compared with the control treatment (both p < 0.001). However, the AM/PM treatment was attributed to a lower feed cost to egg mass compared with the control treatment (p < 0.001). In conclusion, using an AM/PM feeding strategy was found to be economically beneficial.